Bridging the Gap Between Evidence and Argument: Exploring Undergraduate EFL Students’ Struggles with Logical Warrants in Academic Writing - Muthmainnah Mursidin; Ida Ilmiah Mursidin (Prominent, 2026)
The ability to integrate facts and opinions through logical warrants constitutes a fundamental yet frequently neglected competency in undergraduate academic writing. This study investigates the nature and causes of undergraduate EFL students' struggles with logical warrant construction and examines how these difficulties impede broader critical thinking development. Employing a descriptive qualitative design, data were collected from 20 undergraduate students enrolled at Universitas Islam Makassar, South Sulawesi, Indonesia, through three instruments: a Critical Thinking-Based Writing Test, a short essay assignment, and a focused interview protocol. Findings were analyzed using Toulmin's Argumentation Model (2021), focusing on the presence and quality of Claims, Data, and Warrants. The results reveal a profound "Synthesis Crisis": while 85% of participants demonstrated adequate declarative knowledge of the fact-opinion distinction, only 10% succeeded in constructing explicit logical warrants in their argumentative essays. Three interconnected obstacles were identified: (1) the "data-dumping" phenomenon (present in 35% of essays), wherein factual evidence is cited without interpretive purpose; (2) a persistent misconception of academic opinion as purely subjective feeling (observed in 60% of participants); and (3) the wholesale absence of logical warrant construction (documented in 80% of essays). These findings suggest that current EFL writing pedagogy in Indonesian higher education, which predominantly emphasizes structural and grammatical correctness, is insufficient for developing genuine argumentation competency. Implications for curriculum redesign and warrant-focused pedagogical intervention are discussed.